2012
DOI: 10.1088/0004-637x/749/2/118
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Magnetohydrodynamic Simulations of Circumbinary Accretion Disks: Disk Structures and Angular Momentum Transport

Abstract: We present the first three-dimensional magnetohydrodynamic (MHD) simulations of a circumbinary disk surrounding an equal mass binary. The binary maintains a fixed circular orbit of separation a. As in previous hydrodynamical simulations, strong torques by the binary can maintain a gap of radius 2a. Streams curve inward from r 2a toward the binary; some of their mass passes through the inner boundary, while the remainder swings back out to the disk. However, we also find that near its inner edge the disk develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
438
2
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(505 citation statements)
references
References 94 publications
58
438
2
7
Order By: Relevance
“…This precession is due to the highly non-Keplerian nature of the potential close to an unequal-mass eccentric binary such as HD 104237, and is a natural consequence of the fact that orbits in a non-Keplerian potential are not closed ellipses. To date, this effect has only been studied for discs around circular binaries in the context of supermassive black hole (SMBH) binaries (MacFadyen & Milosavljević 2008;Shi et al 2012;D'Orazio, Haiman, & MacFadyen 2013;Farris et al 2014). We find that the precession is uniform between 4 R 6 a b .…”
Section: Simulationsmentioning
confidence: 83%
“…This precession is due to the highly non-Keplerian nature of the potential close to an unequal-mass eccentric binary such as HD 104237, and is a natural consequence of the fact that orbits in a non-Keplerian potential are not closed ellipses. To date, this effect has only been studied for discs around circular binaries in the context of supermassive black hole (SMBH) binaries (MacFadyen & Milosavljević 2008;Shi et al 2012;D'Orazio, Haiman, & MacFadyen 2013;Farris et al 2014). We find that the precession is uniform between 4 R 6 a b .…”
Section: Simulationsmentioning
confidence: 83%
“…Numerical simulations have extensively shown that the SMBHB's orbital motion gives rise to enhanced periodicity in the mass accretion rates onto each black holes (e.g., Hayasaki et al 2008Hayasaki et al , 2013Shi et al 2012;Farris et al 2014 and references therein). This motivates systematic searches of SMBHB candidates through periodic optical variability (e.g., Graham et al 2015a;Liu et al 2015).…”
Section: Smbhb Modelmentioning
confidence: 99%
“…Binaries with 0.3 ∼ < q ∼ < 0.8 clear a lopsided central cavity in the disc, causing variability on three time-scales. The dominant period, (3 − 8)t bin is that of an over dense lump, orbiting at the ridge of the cavity, with additional periodicities at t bin and ≈ 0.5t bin (MacFadyen & Milosavljević 2008;Shi et al 2012;Noble et al 2012;Roedig et al 2012;D'Orazio et al 2013;Farris et al 2014). The dominant period depends on the size of the cavity, and thus on disc parameters, such as temperature and viscosity.…”
Section: Introductionmentioning
confidence: 99%